Unleashing the power of mechanization - Diao, Xinshen; Cossar, Frances; Houssou, Nazaire; Kolavalli, Shashidhara (International Food Policy Research Institute, 2019)
As in most of Africa, agricultural mechanization in Ghana has been slow to develop, either in the form of animal or tractor power. But this has changed markedly since the early 2000s, and today about one third of all Ghana’s farmers report using some form of mechanization, mostly tractors for land preparation, as do over half the farmers with five or more hectares of cropped land. However, policymakers often are skeptical of the role played by the private sector in providing mechanization services and worry that supplyside issues may be constraining its uptake, especially amongst smaller-sized farms. With this in mind, the government recently started to directly engage in the importation and subsidization of tractors, and has established a network of subsidized agricultural mechanization service centers around the country (Diao et al. 2014). The government program operates in direct competition with an already established private sector supply system, and this raises a number of important questions. In particular, is the government program overcoming some inherent market failure problems or is it introducing market distortions in machinery prices, encouraging rent-seeking behavior and possibly crowding out more efficient private suppliers? If the latter, then as suggested in Chapter 6, the program may be an unnecessary and costly addition to the financial burden of the public sector.